Is the grass really greener on the other side? - Lane, Wade Howard (Percy FitzPatrick Institute of African Ornithology, 2018)
While many studies focus on identifying pollutants within an ecosystem or how they affect primary producers, few look at how pollutants move through trophic levels or their influence on animal demography. The aim of this study was to determine whether additional nitrogen, phosphorus and water, to a savanna would alter the vegetation quality enough to influence the feeding behaviour and diet of the ungulate populations both of which would alter the vegetation quantity. The study was conducted in the Kruger National Park. One site was supplied with additional nutrients and compared to three control sites. The nitrogen and phosphorus content of grass and tree leaves collected at the enriched site were higher than the leaves collected at the control site, indicating the additional nutrients are improving the vegetation quality. Feeding rates (determined from photos captured by camera traps) indicated a higher degree of herbivory at the enriched site. However, there was no difference in the δ¹³C value, nitrogen and phosphorus content in the ungulate dung collected amongst the study sites suggesting no change in the diet. The dominant grass was significantly shorter at the enriched site suggesting that increased grazing was diminishing grass biomass. Basic assessment of the trees indicated that the additional water at the enriched site seemed to be triggering an earlier start to the growing season for the trees. It was concluded that the additional nutrients have altered the vegetation structure enough to potentially influence animal demographics.